The Influence of Glutathione-S-Transferase M1 (GSTM1) Null Polymorphism in Acute Leukemia in Sudanese - Mosab Nouraldein Mohammed Hamad (جامعة الشيخ عبدالله البدري, 2020)
Introduction: The glutathione S-transferase (GST) play a crucial role in detoxification of mutagens and carcinogens, including those associated with increased risk of the acute leukemia. Both GST M1 (GSTM1) and GST theta 1 (GSTT1) genes have a “null” variant allele, in which the entire gene is absent. Previous studies have revealed significant differences between populations for genotypic frequen cies of glutathione S-transferase, including (GSTM1) polymorphisms in health and disease. Therefore, we aimed to test whether the GSTM1 null genotype could alter the risk to develop acute leukemia in Sudan. Method: Observational analytical retrospective case-control association study was conducted, over a period of five months. A total of 100 donors/patients were randomly enrolled from different hospitals in Khartoum, Sudan. For molecular analysis genomic DNA was extracted from EDTA blood samples and analyzed by allele specific PCR for demonstration of GSTM1 gene. Results: The data analysis revealed that GSTM1 null genotype is demonstrated in 58% of cases (58% males and 42% females) and in 41% of control subjects (70% males and 30% females). It was observable that the GSTM1 null genotype was higher in cases com pared to controls (odd ratio = 1.915, 95% CI 0.8629 to 4.251). However, the difference showed no significant association between GSTM1 Null and acute leukemia (P = 0.1085). The frequency of GSTM1 null genotype in AML-subtype was significantly higher than ALL- subtype (P = 0.0015). Conclusion: Our findings came up without statistical significant influence of GSTM1 null genotype on the risk of developing acute leukemia in Sudanese, however, the influence cannot be ruled out, so further study with a larger sample size is recommended.